Fontan circuit fenestration occlusion with Occlutech patent ductus arteriosus occluder - Makrexeni, Zongezile Masonwabe; Pepeta, Lungile (SA Heart Journal, 2018)
We present a case of Fontan fenestration closure using an Occlutech patent ductus arteriosus occluder. The patient was diagnosed with tricuspid atresia, pulmonary atresia and secundum ASD at birth. He had a bilateral modified Blalock-Taussig shunt to promote growth of hypoplastic branch pulmonary arteries. He had a bidirectional Glenn Shunt at 11 years of age, and a total cavo-pulmonary connection (TCPC) with a fenestration at 19 years of age. He presented a year later with severe exercise intolerance and cyanosis. Cardiac catheterisation showed hypoxemia, normal pulmonary pressures, patent Fontan circuit and branch pulmonary arteries, and a Fontan circuit-to-right atrium fenestration with right to left shunting. A short shank Occlutech PDA occluder with a waist of 8mm, a pulmonary end of 10mm, an aortic disk of 16mm, and a length of 7mm, was selected to close the fenestration through the transvenous approach. The fenestration achieved complete immediate occlusion with this device.